Primary versus Secondary Psychiatric Disorders: A Typical Case presentation (Indian Journal of Case Reports, 2019)
Psychotic features like delusions, hallucinations, disorganized behavior, disorganized speech and negative symptoms like anhedonia, restricted affect can also appear in secondary medical conditions causing psychosis. Here, we present the case of psychotic symptoms in correlation with a medical condition of subclinical hypothyroidism in a 28-years-old female having an illness for 5 years. This patient presented with psychotic symptoms and did not show any symptomatic improvement with antipsychotics in the past. We reached to clinical suspicion of anti-thyroid psychosis or subclinical hypothyroidism with psychosis on the basis of a slight elevation in thyroid stimulating hormone levels and high titers of anti-thyroid peroxidase antibodies. Levothyroxine was augmented in her treatment regime and she started showing improvement in her symptoms.Levothyroxine, Subclinical hypothyroidism, Thyroid peroxidase antibody.